(untitled) (Razão e Fé, 2023)
The current article aims to present the philosophical vision of Auguste Comte, the founder of positivism, about history and science, reconciling both in the formation of a logical, philosophical and political system, with the aim of reorganizing society on new bases. For this, we delve deeply into the author’s influences, as well as we seek to analyze in detail, despite critically, the formulations about the law of three stages, the law of progress and its relationship with order, its conception of knowledge, the classifi cation of the sciences and its Social Physics, which embody this important and relevant philosophical conception.